MEXICO IN THE PRE-WAR INTERNATIONAL LABOR CONFERENCES (1937-1939) (Tzintzun, Revista de Estudios Históricos, 2022)
The article studies the formation, instruction and performance of the Mexican tripartite delegations (government, workers and employers) in the last International Labor Conferences of the Interwar period. Its main aim is to analyze the conditions of collaboration with the International Labor Organization in the decade after the Mexican incorporation to the international organizations with axis in the League of Nations. The attention paid to the International Labor Conferences prior to the Second World War tries to deepen the analysis of the political and diplomatic criteria of the learning process of Mexican diplomacy in this multilateral sphere.
Keywords: International Labor Conference; International Labor Organization (ILO); International Labor Office (BIT); Mexico; interwar period